A Generalization of the Fuglede-Putnam Theorem to Unbounded Operators. (25th March 2015) - Paliogiannis, Fotios C.
Abstract : LetN, M be unbounded normal operators in a Hilbert space and letT be a closed operator whose domainD ( T ) contains the domain ofN, and the domainD ( T * ) contains the domain ofM . It is shown that ifT N ⊆ M T, thenT N * ⊆ M * T .